Assessing Investment Decisions and Stock Performance Using Neurolinguistic Programming in the Indonesian Capital Market - Rizad Almaliq Mohammad Khan; Ida Busnetty; Sumiyarti Sumiyarti (Eduvest - Journal of Universal Studies, 2025)
This study investigates the influence of Neuro-Linguistic Programming (NLP) techniques on investment decisions and stock performance in the Indonesian capital market. It highlights psychological factors in investor behavior, particularly cognitive biases leading to irrational decisions. NLP application enables better emotional management, enhanced decision-making, and improved outcomes. The quantitative study used surveys and interviews with 150 retail investors from Indonesian stock communities, trading groups, and certification institutes, selected via purposive sampling (maximum two years' experience). Partial least squares structural equation modeling (PLS-SEM) tested relationships between NLP, decisions, and performance. Findings show NLP significantly impacts both (, on decisions; , on performance). Investment decisions also influence performance (, ) and partially mediate the NLP-performance link (, ). This contributes to behavioral finance by integrating NLP into investment psychology. Practically, financial institutions should offer NLP training to help novice retail investors—who dominate the market—manage emotions, reduce biases, and boost portfolio performance.